A cross-sectional examination of the prevalence of psychotropic medications for people living with dementia in Australian long-term care facilities: issues of concern. (4th December 2017) - McMaster, Mitchell; Fielding, Elaine; Lim, David; Moyle, Wendy; Beattie, Elizabeth; ,
ABSTRACT: Background: Behavioral and psychological symptoms of dementia (BPSD) are a common problem in long-term care facilities (LTC). Clinical guidelines dictate that first-line treatments for BPSD are psychosocial and behavioral interventions; if these are unsuccessful, psychotropic medications may be trialed at low doses and their effects can be monitored. Methods: There have previously been no studies with nationally representative samples to investigate psychotropic administration in LTCs in Australia. This study determines the prevalence of psychotropic administration in a representative stratified random sample of 446 residents living with dementia from 53 Australian LTCs. Questionnaire and medical chart data in this study is drawn from a larger cross-sectional, mixed methods study on quality of life in Australian LTCs. Results: It was found that 257 (58%) residents were prescribed psychotropic medications including: antipsychotics ( n = 160, 36%), benzodiazepines ( n = 136, 31%), antidepressants ( n = 117, 26%), and anti-dementia medications ( n = 9, 2%). BPSD were found to be very common in the sample, with 82% ( n = 364) of participants experiencing at least one BPSD. The most prevalent BPSD were depression ( n = 286, 70%) and agitation ( n = 299, 67%). Conclusions: Although detailed background information was not collected on individual cases, the prevalence found is indicative of systematic industry-wide, over-prescription of psychotropic medications as a first-line treatment for BPSD. This study highlights a clear need for further research and interventions in this area.